2015
DOI: 10.1007/s11999-014-4106-8
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Opening-wedge Distal Femoral Osteotomy: Pain Relief, Functional Improvement, and Survivorship at 5 Years

Abstract: Background Distal femoral varus osteotomy may be used to treat valgus knee malalignment or to protect a knee compartment in which cartilage restoration surgery (such as osteochondral or meniscus allografting) has been performed. Medial closing-wedge osteotomy has demonstrated good success in treatment of osteoarthritis in published series, but few studies have evaluated distal femoral lateral opening-wedge osteotomy in terms of correction of deformity, pain and function, and survivorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
97
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 20 publications
(44 reference statements)
2
97
0
1
Order By: Relevance
“…Specifically, this article documented a 3% nonunion rate with no delayed unions [1], which is significantly less than a prior study suggested [3]. This nonunion occurred in the arthrosis subgroup and was ultimately treated with conversion to TKA.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Specifically, this article documented a 3% nonunion rate with no delayed unions [1], which is significantly less than a prior study suggested [3]. This nonunion occurred in the arthrosis subgroup and was ultimately treated with conversion to TKA.…”
mentioning
confidence: 67%
“…However, the lateral opening-wedge distal femoral osteotomy may have advantages including a single osteotomy cut, possible reduced neurovascular risk, and improved correction control due to increased flexibility during intraoperative corrective degree adjustments. Other questions exist including: (1) What are the specific indications and subsequent outcomes of the varus-producing distal femoral osteotomy for joint restoration and valgus gonarthrosis? (2) Which distal femoral osteotomy technique (lateral opening-wedge versus medial closing-wedge) may optimize these outcomes?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The available literature regarding DFO is limited and heterogeneous, but good clinical outcomes have been reported in different studies (8)(9)(10)(11). However, there are still some debated issues, such as the best surgical technique (closing or opening-wedge osteotomy), the type of fixation, the amount of correction to achieve, and the need for a biological graft to fill the osteotomy gap (7).…”
Section: Roberto Rossimentioning
confidence: 99%
“…Cameron et al compared outcomes of simple DFO and DFO associated with joint preservation techniques (osteochondral allograft transplantation and/ or meniscal allograft transplantation) and demonstrated a higher survivorship in the second group (five-years survivorship: 74% in the arthritis group and 92% in the joint preservation group) (10).…”
Section: Indications and Contraindicationsmentioning
confidence: 99%